The Impact of Capital Structure and Profitability on Stock Prices in The Property Sector Companies and Real Estate Listed on The Indonesia Stock Exchange - Alya Innasya Puteri; Elmiliyani Wahyuni (Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2023)
The purpose of this study was to determine the effect of capital structure through the Debt-to-Equity Ratio (DER) and profitability through Return on Equity (ROE) on stock prices in property and real estate sector companies on the Indonesia Stock Exchange (IDX) for the 2016-2021 period. This type of research is field research (field research). By using a quantitative descriptive approach to describe the effect of capital structure, and profitability on stock prices of Property and Real Estate companies for the 2016-2021 period. The population in this study was 86 Property and Real Estate companies. With the purposive sampling technique, only 32 companies were sampled in this study. Data collection techniques use documentation techniques in the form of Annual Reports, statistical reports on annual stock movements, and other data through the Indonesia Stock Exchange website for 6 years. The results of the research that the authors obtained indicate that the Capital Structure through the Debt-to-Equity Ratio (DER) on stock prices. Profitability through Return on Equity (ROE) on stock prices has a negative effect. Capital Structure through Debt-to-Equity Ratio (DER) and Profitability through Return on Equity (ROE) can jointly affect the Stock Price. Based on the results of the coefficient of determination test, it is known that stock prices are influenced by capital structure and profitability by 3.4% while the remaining 96.6% is influenced by other variables outside of this study. Whereas the things that can affect changes in the price of shares are Return on Asset (ROA), return On Equity (ROE), Debt To Asset Ratio (DAR), Debt To Equity Ratio (DER), Book Value Per Share (BVS), Price Book Value (PBV), and Earning Per Share (EPS).